2011
DOI: 10.1158/1535-7163.mct-10-0385
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies on the Mechanism of Action and the Anti-Lymphoma Activity of the Novel Anti-CD20 Antibody GA101

Abstract: GA101 is a novel glycoengineered Type II CD20 monoclonal antibody. When compared with rituximab, it mediates less complement-dependent cytotoxicity (CDC). As expected for a Type II antibody, GA101 appears not to act through CDC and is more potent than the Type I antibody rituximab in inducing cell death via nonclassical induction of apoptosis cytotoxicity, with more direct cytotoxicity and more antibody-dependent cell-mediated cytotoxicity. We evaluated the antitumor activity of GA101 against the human-transfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 38 publications
7
80
0
1
Order By: Relevance
“… 102 Humanized IgG1   Enhanced B-cell depletion in spleen and lymph nodes of cynomolgus monkeys over rituximabDalle et al. 131     Enhanced tumor growth inhibition over rituximab in human-transformed follicular lymphoma RL model in SCID mice. RituximabCD20afucosylatedCommercial rituximab treated with endoglycosidase/fucosidase to generate GlcNAc-rituximabEnhanced depletion of huCD20 + B cells in an FcγR-humanized mouse model over original rituximabLi et al. 70 Chimeric IgG1     GBR 401CD19Reduced (∼50%)CHO cells with reduced fucosylationEnhanced B-cell depletion over rituximab in xenografted SCID mouseBreton et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“… 102 Humanized IgG1   Enhanced B-cell depletion in spleen and lymph nodes of cynomolgus monkeys over rituximabDalle et al. 131     Enhanced tumor growth inhibition over rituximab in human-transformed follicular lymphoma RL model in SCID mice. RituximabCD20afucosylatedCommercial rituximab treated with endoglycosidase/fucosidase to generate GlcNAc-rituximabEnhanced depletion of huCD20 + B cells in an FcγR-humanized mouse model over original rituximabLi et al. 70 Chimeric IgG1     GBR 401CD19Reduced (∼50%)CHO cells with reduced fucosylationEnhanced B-cell depletion over rituximab in xenografted SCID mouseBreton et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“…2 Since the development of rituximab, considerable efforts have been made to design new CD20 mAbs, resulting in the recent approval of next-generation, fully humanized Abs ofatumumab and obinutuzumab. Although these Abs showed better activity in vitro and in xenograft models, 3 results from the present clinical trials are unclear as to whether they are better than rituximab, as these novel Abs were used at an optimized pharmacokinetic schedule, but the rituximab schedule was not pharmacokinetically optimized. 4,5 This suggests novel approaches are urgently needed to improve the efficacy of the current anti-CD20 Ab-based therapies.…”
Section: Introductionmentioning
confidence: 76%
“…Each treatment was continued for 2 consecutive weeks on a daily basis. Mice were followed for survival or until tumor volume reached 1500 mm 3 . Tumor size was measured using standard calipers, and tumor volume was calculated using a modified ellipsoid formula, where volume 5 0.52 3 (length 3 width 2 ).…”
Section: Mice Studiesmentioning
confidence: 99%
“…However, very recently the mechanism of action was described as nonapoptotic lysosomal-dependent cell death (67). In vitro, GA101 seems to show higher antitumor activity against CD20-positive cells compared with rituximab (64,(67)(68)(69)(70). Therefore, through its ability to bypass the apoptotic machinery, GA101 may help to eradicate tumors that are resistant to apoptosis and respond poorly to chemotherapy or immunotherapy.…”
Section: How Does Rituximab Act In Combination With Chemotherapy?mentioning
confidence: 99%
“…Therefore, through its ability to bypass the apoptotic machinery, GA101 may help to eradicate tumors that are resistant to apoptosis and respond poorly to chemotherapy or immunotherapy. In phase I trials, GA101 has been shown to be well tolerated and active in patients with heavily pretreated, end-stage B-cell malignancies (66)(67)(68)(69)(70)(71)(72)(73) and to induce rapid B-cell depletion and substantial tumor response in patients with relapsed-refractory CLL (74). Ongoing phase III trials will confirm whether GA101 efficacy is improved versus current rituximab-based standards of care.…”
Section: How Does Rituximab Act In Combination With Chemotherapy?mentioning
confidence: 99%